2020
DOI: 10.12688/f1000research.24302.1
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Primary melanoma of the gastroesophageal junction

Abstract: Primary malignant melanoma represents the fifth most common cancer in the United States. It is subdivided into two forms: cutaneous (90%), visceral (8%, including ocular and mucosal) and of unknown primary (2%). The vast majority of gastrointestinal melanomas are secondary lesions until proven otherwise. Primary esophageal melanoma in particular is exceedingly rare, less than 200 cases have been documented in the literature to date. It is highly prevalent in Japan and occurs twice as much in men than wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
(24 reference statements)
0
5
0
1
Order By: Relevance
“…По всему миру было описано не более 400 случаев, большинство из которых представляют собой клинические наблюдения [4]. ПМП преимущественно встречается у мужчин (соотношение мужчин и женщин составляет примерно 1,6-2:1) в возрасте 60-70 лет, несколько чаще среди населения Японии [5]. Опухоль преимущественно локализуется в средней и нижней трети пищевода.…”
Section: первичная меланома пищеводаunclassified
“…По всему миру было описано не более 400 случаев, большинство из которых представляют собой клинические наблюдения [4]. ПМП преимущественно встречается у мужчин (соотношение мужчин и женщин составляет примерно 1,6-2:1) в возрасте 60-70 лет, несколько чаще среди населения Японии [5]. Опухоль преимущественно локализуется в средней и нижней трети пищевода.…”
Section: первичная меланома пищеводаunclassified
“…Ishizaki et al ( 9 ) reported a primary malignant melanoma of the esophagogastric junction: the patient was misinterpreted as undifferentiated carcinoma or malignant lymphoma preoperatively and died 11 months after the stomach operation due to multiple metastases. In another similar case ( 3 ), the patient died two months after hospital dismissal. Herein, we report a case of primary gastroesophageal junction melanoma with local lymph node metastasis in an elder Chinese woman.…”
Section: Introductionmentioning
confidence: 96%
“…Mucosal melanoma accounts for less than 1.5% of all melanomas ( 2 ), with only 1% and 0.5% growing in stomach and esophagus in all non-cutaneous melanoma respectively. Primary mucosal malignant melanoma (PMMM) located in the gastroesophageal junction is even rarer, and up to 2020, there are only 7 similar cases ( 3 ). However, once rooted in the esophagus or gastrointestinal tract, the probability of occurrence is small but the possibility of metastasis becomes high ( 4 - 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Malignant melanoma is a disease with poor prognosis that develops from melanocytes of the skin, oral cavity, nasal cavity, pharynx, uvea, and rectum. Primary melanoma of the gastrointestinal tract is rare [ 1 – 3 ], particularly in patients with melanoma esophagogastric junction of which there has been few case reports [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…melanoma of the gastrointestinal tract is rare [1][2][3], particularly in patients with melanoma esophagogastric junction of which there has been few case reports [4,5].…”
mentioning
confidence: 99%